The effect of acupuncture on pain and duration of vaginal delivery: a single-blind randomized clinical trial - Mohammad Reza Hashtroudi; Maryam Rahimi (Mashhad University of Medical Sciences, 2022)
Introduction: Fear of labor leads to an excessive increase in cesarean section. Due to the many maternal and fetal complications of pharmacological analgesia, mothers tend to use non-pharmacological methods. The present study was performed aimed to investigate the effects of acupuncture on labor pain intensity.Methods: This randomized clinical trial study was conducted on 32 pregnant women in Shahid Akbarabadi Hospital in Tehran during 2020-2021. The subjects were randomly allocated into two groups: "real" acupuncture and "pseudo" acupuncture. The women were evaluated during active phase of labor and compared for pain intensity before, 15, 30, and 45 minutes after acupuncture. Visual Analogue Scale (VAS) was used to assess pain. Data were analyzed by SPSS software (version 18) andChi-square and Student t-test. P<0.05 was considered statistically significant.Results: The mean pain intensity of the case group was less than the control group at 30 and 45 minutes after acupuncture (P=0.045) and (P<0.001); while before the intervention and in the first 15 minutes after the intervention, there was no significant difference (P=0.29) and (P=0.68), respectively). Acupuncture had no significant effect on neonatal Apgar score and need to oxytocin (p> 0.05). The duration of the second stage of labor in the case and control groups was 193 ± 130 and 305 ±129 minutes, respectively, which was significantly lower in the case group (p = 0.022).Conclusion: Acupuncture is a safe and tolerable method that can reduce labor pain and duration of active phase of labor, while it has no effect on Apgar score and need to oxytocin.